فض المنازعات في الصناعة المالية الإسلامية دراسة مقارنة بين المملكة العربية السعودية وماليزيا - حلواني، محمد خالد عبد الوهاب (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
The study examines the problems related to the Islamic finance system, and its products, the dispute resolution in the Kingdom of Saudi Arabia and Malaysia, and the goals to benefit from the Malaysian experience in this field, both economically and legally. The economic side, it shows that Malaysia is leading the world in Islamic financial products, due to the engagement in building good platforms for Islamic financial products. The study discusses that Malaysia has devised and provided separate systems for Islamic finance. The Malaysian system does not allow Islamic products to mix and become part of the conventional financial system, while the Saudi system mixes between the two aspects of Islamic and conventional bank. This is because that the sources of laws and system in Saudi Arabia are derived from Islamic laws (Shariah) and its sources. The study highlights on the laws and regulations which Islamic financial disputes are resolved in both countries, where it has been shown that Malaysia well organised in this regard, while Saudi Arabia is left within its very narrow limits. This causes a lack of growth and prospency of Islamic finance activities, although Islamic finance practices will enhance Saudi Arabia's economy, leading to the realisation of the 2030 vision of the Kingdom. Also, the study highlights the Islamic judicial systems, administrative judiciary and the bodies and councils which resolve Islamic financial disputes in Saudi and Malaysia, and highlights the local and international jurisdiction in both countries. The judicial authority and its stages are also highlighted in its case Malaysia and the jurisdiction of its courts. The research also discusses that the one of the largest international financial centres and companies that quickly boosted Malaysia's Islamic economy is the Labuan International Business and Financial Services Centre (IBFC), which offers a wide range of Islamic and conventional financial products and services, in order to achieve Islamic financial and economic stability orverseas. The study used several approaches, includings are: Analytical approachs: by studying the rules and laws related to Islamic products in Saudi Arabia and Malaysia, and the provisions related to the regulation of the Islamic financial analytical approachs. The study also reviewed various of encyclopedias, books, articles, various publications, regulations, laws, decisions and rulings related to the Islamic financial industry in Saudi Arabia and Malaysia. The study also used the comparative methods: by comparing existing laws in the Kingdom Saudi Arabia and Malaysia, and identify the strengths and weaknesses as well as differences between the Islamic financial systems in both countries. The research has answered several scientific questions, which are: what is the most important concepts of settling disputes in Islamic financial products? And what is the reality of the Islamic financial products in both Malaysia and Saudi Arabia, and its role in developing Islamic financial products globally? The research also examines the rules and regulations related to Islamic banking in Saudi Arabia and Malaysia. The inductive method is used to analyse the subject to monitor and study the scientific efforts and comparative the strengths and weaknesses. Finally, the research revealed a number of important findings, including that the alternative means of resolving disputes resolution in Islamic financial products represent great legislatives assets that can achieve the interests of all parties.